If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h + 6k + -3 + h + -7k = 0 Reorder the terms: -3 + 5h + h + 6k + -7k = 0 Combine like terms: 5h + h = 6h -3 + 6h + 6k + -7k = 0 Combine like terms: 6k + -7k = -1k -3 + 6h + -1k = 0 Solving -3 + 6h + -1k = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 6h + 3 + -1k = 0 + 3 Reorder the terms: -3 + 3 + 6h + -1k = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 6h + -1k = 0 + 3 6h + -1k = 0 + 3 Combine like terms: 0 + 3 = 3 6h + -1k = 3 Add 'k' to each side of the equation. 6h + -1k + k = 3 + k Combine like terms: -1k + k = 0 6h + 0 = 3 + k 6h = 3 + k Divide each side by '6'. h = 0.5 + 0.1666666667k Simplifying h = 0.5 + 0.1666666667k
| 4x(x+8)-5(x+8)=0 | | s+t+t+s-s= | | 9MPH=10MILES | | 5y^2+4y+12=0 | | 45-5x=13-9x | | 6y-3=7+y | | 3+9x=-37+x | | 20y+1=45 | | 87=y+15+y | | X=8+23 | | 6(3k+2)-3(k+5)= | | 30=4x+5y | | x=30-5y | | (x+9)(2x-10)=0 | | 4+11x=-46+x | | 8z+9=8 | | 2x+2y+4z=6 | | 20y+4=20 | | 6x-(2x+3)= | | 0.04-x^2=0 | | 0.16+0.8x+x^2=0 | | 9x=2* | | 4x-19=9x+9 | | 9(a+9)=135 | | 23=3c-1 | | 5+66x=33x+17 | | 7e-6=8 | | 7(x-7)=-45.5 | | 2(a+7)=27.6 | | 7m-26=44 | | 8.8=4c-4 | | 6e-7=27.2 |